Comparative investigation of ductile fracture with 316L austenitic stainless steel in small punch tests: Experiments and simulations. (December 2018) - Kubík, Petr; Šebek, František; Petruška, Jindřich; Hůlka, Jiří; Park, Namsu; Huh, Hoon
Highlights: Wide range of stress states is experimentally described for AISI 316L. Detailed study of fracture surfaces produced by penetration tests. Non-standard cracking is observed due to ferrite phase. Uncoupled ductile fracture criteria are calibrated for austenitic stainless steel. Abstract: This paper deals with a small punch test and ductile failure prediction of austenitic stainless steel 316L. Comprehensive investigation of fracture surfaces was conducted as well as examination of δ-ferrite and σ-phase present in the material in order to reveal the reason of occurrence of nonstandard type of fracture. Three phenomenological ductile fracture criteria were selected for comparative simulations regarding the prediction of crack initiation and propagation during the SPT. These criteria were calibrated by using the fracture tests of smooth cylindrical specimens, notched cylindrical specimens, notched tube specimens and cylinders with spherical recess. The whole material model including the fracture criteria with von Mises plasticity and element deletion technique for simulation of the crack initiation was implemented by using the user subroutine Vectorised User MATerial into the commercial finite element code of Abaqus. Finally, the simulation results with three ductile fracture criteria are compared and discussed based on the experimental results. Only one of the failure criteria captured the displacement at fracture correctly.